2007
DOI: 10.1177/0306624x06294137
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Art Therapy in Reducing Depression in Prison Populations

Abstract: Major obstacles block the effectiveness of therapy in prison. Many inmates have an inherent mistrust for verbal disclosure. Rigid defenses exist for basic survival. Despite these defenses, there has been support for art therapy as a valuable tool. Unfortunately, there has been little research to measure the effectiveness of art therapy in prison. Two quantitative studies were initiated in a North Florida prison to measure the effectiveness of art therapy with inmates, specifically in decreasing depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 9 publications
1
90
0
14
Order By: Relevance
“…They concluded that bibliotherapy could be used as an adjunct to conventional therapies (Cuijpers et al 2010). Art therapy can be defined as the therapeutic use of art making, within a professional relationship, by people who experience illness, trauma, or challenges in living (Gussak 2007). Art therapy helps to overcome psychological disabilities through nonverbal treatment methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that bibliotherapy could be used as an adjunct to conventional therapies (Cuijpers et al 2010). Art therapy can be defined as the therapeutic use of art making, within a professional relationship, by people who experience illness, trauma, or challenges in living (Gussak 2007). Art therapy helps to overcome psychological disabilities through nonverbal treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, an art therapy intervention enhanced psychological well-being by decreasing negative emotional states and enhancing positive ones in a group of older women with breast cancer (Puig et al 2006). Also, in another study, they conducted art therapy program for prison populations and founded that there was a significant decrease in depressive symptoms in those inmates who participated in the program (Gussak 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In general, articles located via the education database ERIC were more focused on practice than outcome, and more on practitioners' rationale than on empirical results. One article was sourced direct from the author (Gussak, 2007), when it became apparent that this was more useful to the project than another by that author previously located through our searches.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analytical studies (Khodayarifard & ShokoohiYekta, 2010) have revealed that cognitive-behavioural intervention methods have good impact on inmates. These studies demonstrated that there were apparent improvement in mood, behaviour, and problem-solving, an increase in independence, a decrease in depressive symptoms, and also appropriate identity within the group dynamic (Gussak, 2004;2007;2009 in Ismail, Abd. Manaf & Jaafar, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…An abundant of studies had been carried out to examine the benefits of art therapy and cognitive behaviour therapy with prison inmates in many countries (Kendall, 1993;Gussak, 2004;2007;2009, Clark, 2010; Kobayashi, Matsumoto, Imamura, Wada, Ozaki, Takeuchi, Hasegawa, Imamura, Tania & Adachi, 2011; Akpama, 2013). Meta-analytical studies (Khodayarifard & ShokoohiYekta, 2010) have revealed that cognitive-behavioural intervention methods have good impact on inmates.…”
Section: Introductionmentioning
confidence: 99%